Value Creation in Public Enterprises: An Empirical Analysis of Coordinated Organizational Changes in the Veterans Health Administration - Thibodeau, Nicole; Evans, John H. (Harry); Nagarajan, Nandu J.; Whittle, Jeff (The Accounting Review, 2007)
As part of a federal government initiative to increase efficiency and quality, in 1996 the United States Veterans Health Administration (VHA) radically restructured its organizational design and management processes. This study uses 1992–1998 clinical, workload, and financial data to examine the effect of this reform on performance. Several previous government attempts to introduce private sector management practices, such as management by objectives (MBO) or program planning and budgeting system (PPBS), have been largely unsuccessful. In contrast to prior reforms, the current restructuring introduced coordinated changes in the VHA organizational structure, performance measurement, and reward systems. Our results document that, following the reorganization, the VHA cost per patient declined significantly and various quality measures improved. Our analysis suggests that reduction in excess capacity and the more intense use of remaining capacity are among the primary explanations for the VHA achieving the observed cost reductions. These findings suggest that coordinated changes in organizational structure, performance measures, and incentives can create value for public enterprises even though control mechanisms are generally more limited in these environments than in the private sector.